Napabucasin Induces Mouse Bone Loss by Impairing Bone Formation via STAT3 - Huang, Xiangru; Jin, Anting; Wang, Xijun; Gao, Xin; Xu, Hongyuan; Chung, Miri; Dai, Qinggang; Yang, Yiling; Jiang, Lingyong (Frontiers in Cell and Developmental Biology, 2021)
The novel small molecule Napabucasin (also known as BBI608) was shown to inhibit gene transcription driven by Signal Transducer and Activator of Transcription 3 (STAT3), which is considered a promising anticancer target. Many preclinical studies have been conducted in cancer patients examining the selective targeting of cancer stem cells by Napabucasin, but few studies have examined side effects of Napabucasin in the skeleton system. In the present study, we found treating bone marrow mesenchymal stem cells (BMSCs) with Napabucasin in vitro impaired their osteogenic differentiation. In terms of mechanisms, Napabucasin disrupted differentiation of BMSCs by inhibiting the transcription of osteogenic gene osteocalcin (Ocn) through STAT3. Moreover, through micro-CT analysis we found 4 weeks of Napabucasin injections induced mouse bone loss. Histological analysis revealed that Napabucasin-induced bone loss in mice was the result of impaired osteogenesis. In conclusion, this study provided evidence for the effect of Napabucasin on mouse bone homeostasis and revealed its underlying mechanisms in vivo and in vitro.